Determination of trace cadmium in saliva samples using spray assisted droplet formation-liquid phase microextraction prior to the measurement by slotted quartz tube-flame atomic absorption spectrophotometry - Topal, Serkan; Saylan, Meltem; Zaman, Buse Tugba; Bakirdere, Sezgin (ELSEVIER GMBH, 2021)
Background: An effective, green and rapid analytical strategy namely the simultaneous spray assisted droplet formation-liquid phase microextraction (S-SADF-LPME) method was developed for the determination of trace quantity of cadmium in saliva samples by using the slotted quartz tube-flame atomic absorption spectrophotometry (SQT-FAAS). By the developed method, external dispersive solvent usage for droplet formation was reduced to obtain a more environmental-friendly method. Methods: Method consists of a simultaneous complexing and extraction step, which was based on spraying an extraction solvent containing a solid ligand into the aqueous sample solution, forming fine droplets without the use of dispersive solvent. The procedure was implemented using a customized, cost effective and portable spray apparatus to minimize the consumption of reagent, analysis time and operation steps. Thus, this methodology ensures better repeatability and accuracy while minimizing the relative errors caused by the experimental steps. Parameters including the buffer amount, extractant/ligand concentration, extraction solvent type, extraction/ ligand solution volume, spraying number and vortex period were systemically optimized to lower the detection limit. Results: Under the optimal extraction conditions, 96.9-folds enhancement in the detection power of the traditional FAAS was achieved. The limit of detection and limit of quantification values of presented method were calculated to be 0.65 and 2.17 ng mL-1, respectively. Accuracy and applicability of the optimized method was investigated by collecting saliva samples from smokers. Satisfactory percent recovery values wereachieved for cadmium with a low standard deviation in the acceptable range of 84.9-109.6 %. Conclusion: The developed dispersive solvent-free S-SADF-LPME technique presents a fast, simple, cost-effective and eco-friendly microextraction method based on the use of an easily accessible and functional spray apparatus.
Keywords: Cadmium; Saliva; Slotted quartz tube-flame atomic absorption; spectrophotometry; Microextraction; CLOUD POINT EXTRACTION; BIOLOGICAL SAMPLES; LEAD; SPECTROMETRY; BLOOD; ELEMENTS; URINE; PRECONCENTRATION; COPPER(II); VALIDATION; Biochemistry & Molecular Biology; Endocrinology & Metabolism